PENGAYAAN MATERI SIARAN AGAMA UNTUK KERUKUNAN UMAT BERAGAMA PADA RADIO-RADIO SWASTA DI KALIMANTAN SELATAN - Surianor . (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Religion Islam is very rich with the material teachings about religious harmony, especially in relationships with adherents of other religions. But regrettably the propagation material about this harmony is still rarely delivered or socialized to the community, including through radio-radio that conducts the broadcast in the community. This paper discusses the teachings of Isam about religious harmony and loading of harmony material through the broadcast of preaching programs on radio stations in South Kalimantan. Conclusion of this paper, the average radio in this area already has the broadcast of Islamic propagation, but the percentage of time is very little compared to other events, and from that little is still rarely filled with religious harmony material. The percentage of da'wah events only ranges from 3-10% of the entire event material, and only Radio Gema Kuripan Amuntai whose da'wah material reaches 15%. In the future, religious teachings on harmony should be broadcasted also through educational and cultural events. Here not only the teachings of religion, but local cultural values that can be harmonized harmony can be broadcast. If the material is well processed, it will be interesting, and more importantly useful for people to improve harmony and avoid the rifts and conflicts nuanced SARA.